Evolution of Persian traditional architecture through the history - Hejazi, Mehrdad; Hejazi, Bina; Hejazi, Saba (Journal of Architecture and Urbanism, 2015)
The architecture of Iran is wholly based on the comprehensive use of knowledge of both metaphysical and physical sciences. Architecture and structural engineering in Iran involve a great range of buildings distributed over a vast area from the borders of China to the Mediterranean coastlines. Certain design elements, developed by Iranian architecture and aesthetics, persisted for thousands of years and exerted a marked effect on other successive styles of construction throughout the world. Architecture in Iran solved complicated structural problems and created magnificent architectural masterpieces. In this paper, the evolution of Persian traditional architecture is discussed and a general overview of the paramount virtues of the traditional architecture and historical buildings of Iran with emphasis on structural and scientific features will be presented.